Transferensi dalam Proses Konseling - Indra Saputra; Rezki Hariko; Yeni Karneli (Indonesian Counselor Association (IKI), 2023)
Transference can be an obstacle and help that counselors get from their clients. However, transference that is too strong from the client will also hinder the relationship in the counseling process. For this reason, a counselor must know what the causes and strategies are to resolve transference in the counseling relationship. Therefore, the purpose of this study is to find out how transference is in the counseling process, to obtain data regarding this purpose, the researcher uses a qualitative method with a descriptive narrative approach with online data collection. The results of this study are transference is a projection of feelings from the client to the counselor, this projection of feelings occurs because of the blurring of ethical standards or boundaries set by the counselor in the counseling process, for that we need several strategies to overcome them.